Complementary compound set-point control by combining muscular internal force feedforward control and sensory feedback control including a time delay. (18th April 2018) - Matsutani, Y.; Tahara, K.; Kino, H.; Ochi, H.
Abstract: This paper proposes a new set-point control method for a musculoskeletal arm by combining muscular internal force feedforward control with feedback control including a large time delay. The proposed method accomplishes robust and rapid positioning with a relatively small muscular force. In the positioning by the muscular internal force feedforward controller, a large muscular force is required to achieve good performance. On the other hand, in the positioning by the feedback controller including the large time delay, the system can easily fall into an unstable state. A simple linear combination of these two controllers makes it possible to improve the control performance and to overcome the drawbacks of each controller in a complementary manner. First, a two-link six-muscle arm model is considered as a musculoskeletal system in this study. Second, the new set-point control method, which consists of the feedforward control signal and the feedback control signal including the time delay, is designed. Third, the stability of the proposed method is investigated using the Lyapunov–Razumikhin method. Finally, the results of numerical simulations and experiments are presented to demonstrate the advantages of the proposed method. Abstract :